Journal Documentary Film "Time Equals Knowledge" Using Expository Type - Christian Chandra Sitorus; Afdhol Dzikri; Oktavianto Gustin (JOURNAL OF APPLIED MULTIMEDIA AND NETWORKING, 2019)
Globalization is a process of world community order that can cause positive and negative impacts. The city of Batam is one of the cities in Indonesia that experienced the impact of globalization on youth, where the lifestyle of its people especially among young people experience change. Apart from the rapid technological developments and modern lifestyle, hanging out is one of the activities that can have negative impact for both themselves and the surrounding community. Some of the factors that cause young people to do that is the influence of friends and do not want to be obsolete, but now there are some young people who still do positive things such as creating a social community that educational, therefore made an information media in the form of a documentary about community of teachers in Batam City. This documentary contains information about a community of teachers who are young people who can use their spare time to provide knowledge and fun to children aged 4 - 15 years. This documentary film aims to change the mindset and behavior of young people in order to take advantage of time with positive activities. This film is expository type using data collection method. The methods include observation, interview and film design consisting of pre production, production and post production. The results of the study prove that documentary film Expository Type can be in the form of media that convey factual information through narratives and images, based on a total percentage of 83.32% that documentary types of Expository Type can function as a medium for delivering messages and factual information for the community, especially young people in the city of Batam.